Effectiveness Of Economic Empowerment Program In Empowered Women Study Group - Alam, Syamsul; Ibrahim, Hasbi; Nildawati; Amansyah, Munawir; Basri, Syahrul; Habibi; Saswini, Andi Ade Ula; Bimantoro, Krisno; Rasyidi, Gunawan (LAA MAISYIR : Jurnal Ekonomi Islam, 2022)
One of the important elements of development that needs attention is social and economic development for women. The role of women in the development of the Islamic economic sector is now very significant. This has had many positive impacts on both sharia economic growth and the Indonesian economy in general. This study aims to determine the effectiveness of the economic empowerment program in empowered women learning groups (KBPB) which is a CSR program of PT. Pertamina Marketing Operation Region VII, Ujung Tanah District, Makassar City. This research uses descriptive quantitative research, with a total sample of 30 respondents. The results showed that 70% of respondents were able to start SME businesses independently after participating in the KBPB program, and 30% had not been able to develop their businesses independently. Based on the perceived changes that 50% of participants were able to develop productive activities in the economic field, 40% strongly agreed that after participating in the program participants were able to self-actualize, and 40% strongly agreed that they were able to collaborate with others to form a business after joining the KBPB program.